METHODS OF UPBRINGING IN THE FAMILY AS AN AREA OF FORMING THE UPBRINGING AWARENESS OF PARENTS ON THE EXAMPLE OF THE FUNCTIONING OF PROFESSIONAL FOSTER FAMILIES IN SZCZECIN - Kazubowska, Urszula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
When implementing educational and socialization processes in the family, each parent uses specific educational methods. Methods of family upbringing are considered to be systematic ways of coexistence and coexistence of everyday life situations of the educator with the pupil in a direct or indirect context marked by family axiology. Family upbringing methods always have an awareness dimension. Family educational activity involves the use of various upbringing methods, selected appropriately for the adopted purpose of upbringing on the basis of a thorough knowledge of the child's mental development properties and in accordance with existing pedagogical knowledge. The aim of the research was to learn methods of parenting preferred in professional foster families in Szczecin. The canon of upbringing methods used by foster parents towards children entrusted to them was sought. The research consisted of three stages: theoretical and methodological conceptualization of research issues, pilot studies and actual research. The empirical material obtained was subjected to quantitative and qualitative analysis along with the desire to make a holistic diagnosis of the family. The upbringing methods most often chosen by foster parents include: the method of direct influence with its various implementation options (modeling, giving children educational tasks, persuasion). Equally often, foster parents used the method of adequate reward and punishment, a method of personal influence and a method of managing self-development (especially towards older children). Generally, the preferred methods of upbringing in professional foster families have a positive dimension and in a constructive way influence the optimal way of exercising upbringing and socialization interactions with children raised in family custody. Analyzing the results of research on the obtained data, the following regularity can be seen. The more positive upbringing methods are appropriate in professional foster families, the higher the level of involvement in family education processes saturated with axiology. What's more, the use of positive methods of education in a foster family directly contributes to raising their educational awareness and optimization of various activities towards children in the family.